Amount of TNF‐α released from macrophages reacting with polyethylene particles showed dose‐dependent relationship to the total surface area of added particles. Issue 4 (12th December 2018) - Shen, Weiqi; Tomita, Naohide; Niikura, Miho; Sugino, Takuma
Abstract : The immune response to ultra‐high molecular weight polyethylene wear debris is thought to be one of the major causes of osteolysis and aseptic loosening. An in‐vitro method for the measurement of the response is necessary in order to priori estimate the lifespan of the implants. It is of importance to distinguish the bioactivity of various polyethylene biomaterials. The current research focused on the inverse culturing process, which was shown to be effective to evaluate the biological reaction of mouse macrophages and wear particles by estimating the amount of inflammatory cytokines. In this study, several improvements were carried out through trial quantification. Silicon sheet was introduced instead of PVC seal to remove air bubbles and to eliminate the influence of potentially‐attached endotoxin. Calculations along with experiments according to Stokes' law were also performed to determine the reaction time and the minimum particle size that can be phagocytosed by macrophages in the improved method. The authors co‐incubated mouse macrophages and polyethylene particles in different sizes, densities and molecular weights using the new method. The result suggests that the amount of tumour necrosis factor‐α (TNF‐α) generated is dosage dependent on the total surface area of particles added regardless of particle size, density and molecular weight of polyethylene.